Activated B Lymphocyte Inhibited the Osteoblastogenesis of Bone Mesenchymal Stem Cells by Notch Signaling - Mengxue Pan; Wei Hong; Ye Yao; Xiaoxue Gao; Yi Zhou; Guoxiang Fu; Yuanchuang Li; Qiang Guo; Xinxin Rao; Peiyuan Tang; Shengzhi Chen; Weifang Jin; et al. (Stem Cells International)
Estrogen is very important to the differentiation of B lymphocytes; B lymphopoiesis induced by OVX was supposedly involved in osteoporosis. But the effects of B lymphocytes on the osteogenic differentiation of bone mesenchymal stem cells (BMSCs) are not clear. In this study, we detected bone quality and bone loss in a trabecular bone by electronic universal material testing machine and microcomputed tomography (micro-CT) in OVX and splenectomized-ovariectomy (SPX-OVX) rats. Additionally, changes in lymphocytes (B lymphocyte, CD4+ and CD8+ T lymphocytes, and macrophages) in the bone marrow were analyzed by flow cytometry. The osteogenesis of BMSCs cocultured with normal and LPS-pretreated B lymphocytes was detected by BCIP/NBT and Alizarin red S staining. Measurement of the Notch2, Notch4, Hey1, Hey2, Hes1, and runt-related transcription factor 2 (Runx2) expression in BMSCs cocultured with B lymphocytes was done using real-time PCR. The effects of dexamethasone and DAPT (inhibitor of Notch signaling) on osteogenesis of BMSCs were detected by BCIP/NBT, Alizarin red S staining, and real-time PCR. Osteoporosis happened in OVX rats, more serious in SPX-OVX rats, B lymphocytes increased in OVX rats, and sharply higher in SPX-OVX rats. Osteoporosis did not happen in SPX rats which is still companied with a high increase of B lymphocytes. LPS-pretreated B lymphocytes suppressed the osteogenesis of BMSCs, but the normal B lymphocytes could not. The LPS-pretreated B lymphocytes upregulated the expression of Notch4, Hes1, and Hey2 and downregulated the expression of Runx2 in BMSCs. Dexamethasone and DAPT could downregulate the high expression of Notch4, Hes1, Hey2 and upregulate the low expression of Runx2 in BMSCs which cocultured with LPS treated B lymphocytes, the inhibited ALP and Alizarin red staining in BMSCs which cocultured with LPS treated B lymphocytes also partly restored.